Double Urethral Valve: a Clinical Case - V. A. Vorobev; V. A. Beloborodov; S. L. Popov (Креативная хирургия и онкология)
Introduction. Urethral valves (UVs) are congenital malformations of the urethra, leading to infravesical obstruction. The most common UV is the posterior urethral valve (PUV). The anterior urethral valve (AUV) is a somewhat rarer, but still well-known congenital anomaly. UVs can provoke significant obstruction of the proximal urinary system, which can later lead to disability of children and more frequent deaths.Materials and methods. The article presents a clinical example of a 32-year-old man with a congenital double urethral valve occuring in the anterior and posterior urethra, which led to the development of chronic urinary retention, urinary tract infection and chronic renal failure. The patient underwent a successful urethroplasty operation to remove the valve mechanism.Results. Six months following surgery, the patient noted the complete disappearance of symptoms, with renal function having returned to normal. No signs of recurrence of the disease or the formation of stricture of the urethra were detected by to the survey.Conclusion. A congenital variant of the double UV is an unusual extremely rare cause of infravesical obstruction. Early diagnosis and treatment of this anomaly is very important for preventing further irreversible damage to the urinary system. The presented clinical observation demonstrates the need to organise and conduct periodic preventive examinations of children of different age groups.